Using Video Modeling, Explicit Instruction, and Augmented Reality to Teach Mathematics to Students With Disabilities. (November 2022) - Morris, Jared R.; Hughes, Elizabeth M.; Stocker, James D.; Davis, Emelie S.
Students with exceptionalities who do not make adequate progress with core instruction in mathematics require more intensive research-based interventions such as explicit instruction or video modeling to address instructional needs. This study examined the effects of combining point-of-view video modeling, explicit instruction, and augmented reality to teach mathematics to students with disabilities. The researchers employed a multiple baseline across skills, single-subject research design to evaluate the effects of the intervention on student performance across four mathematics skills. Two eighth grade students identified as having a disability impacting mathematics, one with autism spectrum disorder and one with a specific learning disability, participated in the study. Visual analysis determined a functional relationship between the dependent and independent variables. Tau-U result for the intervention phase was 1.0 across all four skills for each participant. Participants demonstrated high levels of maintenance, and with one exception, students were able to apply the skills to word problems without additional training. Limitations and implications for future research and practice are discussed.